THE EFFECT OF TRANSFORMATIONAL LEADERSHIP AND COMPENSATION ON PERFORMANCE (Empirical Study of Teachers at Mafazah Modern Boarding School) - Mohammad Mahrum; Ismu Hadjar; Nancy Yusnita (UNIVERSITAS PAKUAN, 2021)
This research is motivated by several interviews with the leadership of the Mafazah Modern Islamic Boarding School, several problems regarding the performance of teachers conveyed by the Head of the Pesantren as informants, including, there are still many teachers who are less disciplined with working hours that have been determined by the staffing department, sometimes in the schedule of admission. work is still late and when the time runs out, the teacher always waits for orders and lacks initiative in work, many teachers complain about the leadership of the head of the pesantren in paying attention to teachers personally, the ineffective use of the facilities provided to support work teachers, many complaints about the current compensation system and the reasons for compensation are factors that reduce teacher performance. This study was conducted to determine the effect of transformational leadership and compensation on teacher performance at the Mafazah Modern Islamic Boarding School. The number of samples used in this study were 140 respondents, using simple linear regression analysis and multiple linear regression. The results show that transformational leadership and compensation affect performance partially and simultaneously.